The Oxford Handbook of Developmental and Life-Course Criminology 2018
DOI: 10.1093/oxfordhb/9780190201371.013.24
|View full text |Cite
|
Sign up to set email alerts
|

Employment, Crime, and the Life Course

Abstract: This chapter focuses on life-course studies of employment and crime. It draws predominantly on quantitative results, but evidence from qualitative life-course studies are discussed as well. The purpose here is to provide an informed assessment of state-of-the-art scholarship. This chapter reviews studies that examine the capacity of employment (job entries) to curb criminal involvement. There are strong theoretical reasons to expect transitions to stable employment to contribute to the desistance process. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Uggen found that the impact of employment on recidivism was near zero for individuals younger than 27 years of age but negative and statistically significant for those 27 or older. These findings have been widely cited (e.g., Apel et al, 2007;Berg & Huebner, 2011;LeBel et al, 2008;Newton et al, 2018;Savolainen et al, 2019;Visher et al, 2005;Zweig et al, 2011), both in speaking to the validity of life-course perspectives and in calls for employment programs in prison and postrelease for formerly incarcerated individuals. This latter point is particularly important as the implications of Uggen's (2000) findings are that "programming providing marginal jobs are unattractive for youth" but "may provide the turning point toward a viable pathway out of crime for older offenders" (p. 544).…”
Section: Life-course Perspective Employment and Crimementioning
confidence: 91%
“…Uggen found that the impact of employment on recidivism was near zero for individuals younger than 27 years of age but negative and statistically significant for those 27 or older. These findings have been widely cited (e.g., Apel et al, 2007;Berg & Huebner, 2011;LeBel et al, 2008;Newton et al, 2018;Savolainen et al, 2019;Visher et al, 2005;Zweig et al, 2011), both in speaking to the validity of life-course perspectives and in calls for employment programs in prison and postrelease for formerly incarcerated individuals. This latter point is particularly important as the implications of Uggen's (2000) findings are that "programming providing marginal jobs are unattractive for youth" but "may provide the turning point toward a viable pathway out of crime for older offenders" (p. 544).…”
Section: Life-course Perspective Employment and Crimementioning
confidence: 91%
“…Studies in the tradition of life course criminology have demonstrated that major events and transitions in individuals' life, such as getting a job and starting a family, are important to understand desistance from criminal careers (e.g., Uggen & Wakefield, 2008;Craig et al, 2014;Skardhamar et al, 2015;Savolainen et al, 2018). Though central to the life course approach, most studies conducted in this field however do not incorporate the notion that people live their lives in the larger context of society where macro-level circumstances change over time (Elder & Giele, 2009).…”
Section: Introductionmentioning
confidence: 99%